DIVERSITY OF TRADITIONAL VILLAGES IN BALI: PARHYANGAN, PAWONGAN AND PALEMAHAN PERSPECTIVES - I Gusti Ngurah Sudiana (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
This study aims to analyze the differences between the three types of traditional villages, both the traditional village of the mountains, the traditional village of Dataran and the traditional village of Pesisir or Anyar from the side of Parhyangan, Pawongan and Palemahan. This is what will be investigated in depth so that people know correctly about this diversity. This research is a descriptive research with data collection methods through observation, in-depth interviews and documentation studies. The results of the study stated that the diversity of traditional villages from the side of Parhyangan, Pawongan and Palemahan cannot be denied that there are differences from one to another. This gave rise to the term Mawacara Negara village, mawa tata, bhina wakya eka sruti, kala patra village or kala tattwa village. That the diversity of traditional villages in terms of Parhyangan, Pawongan and the Palemahan of the meaning is the same in different forms.